Analysis Of Physical And Mechanical Properties Of Recycled Aluminum With Variations In Molding Temperatures And Adding Degasser Powder As An Environmentally Friendly Material - Zainal Abadi; Andre Kurniawan; Andril Arafat; Susi Marisa (Unversitas Negeri Padang, 2025)
Recycling is the process of converting used materials into new materials with the aim of preventing waste that can actually be useful, reducing the use of new raw materials, reducing energy use, reducing pollution, land damage. The purpose of this study was to determine the most optimal pouring temperature to produce the best casting of the physical and mechanical properties of recycled aluminum material added with degasser powder. The urgency of this study is as a research material in the field of materials. This research method is to make 3 variations of melting temperature before pouring into the mold, the temperature variations used are 6750-7000C, 7000-7250C and 7250-7500C. At any temperature variation before pouring into the mold, degasser powder is also added to help clean the molten metal from the gases trapped in the molten metal. After the sample is molded, the results are visually observed, then a specimen is made to test the mechanical properties of the used aluminum casting. The data from the test results show that there is a fairly large porosity value in each variation. The hardness value of the test results shows that it is directly proportional to the temperature variation. At a temperature of 7250-7500C the average hardness value is 98.5 HVN. While the tensile strength at a temperature of 7250-7500C value is 83.58 Mpa, at a temperature of 7000-7250C = 74.39 Mpa and at a temperature of 6750-7000C = 71.5 Mpa. Thus the most optimal temperature in this used aluminum casting is 7250-7500C.